PROFILE OF STUDENT SCIENTIFIC PERFORMANCE IN COMPUTER-BASED LEARNING MEDIA COURSES THROUGH IMPLEMENTATITON OF TEAM BASED PROJECT LEARNING METHODS - Nuraini, Lailatul; Sri Handono Budi Prastowo; Sinta Nuriyah Mahbubiyah Royani (JURNAL PEMBELAJARAN FISIKA, 2025)
Technological advances in the world of education can be used as a means of creating learning media that functions as an innovative and meaningful learning resource for students. This is in line with Kepmendikbud No. 3 of 2021 which mentions the application of learning methods in accordance with IKU Point 7 regarding the application of project-based group learning methods (Team Based Project). This study aims to describe the scientific performance profile of students in computer-based learning media courses through the application of the project-based team learning method. This research method uses descriptive research methods. Research respondents were students taking computer-based learning media courses in the even semester of 2020/2021. Data collection techniques use project assessment sheets (scientific performance), observation and documentation. Data analysis techniques use the percentage of the Likert scale used. The results showed that 85.71% of students were able to plan, implement projects and prepare reports. This means that students are able to provide substantively correct interpretations of the project products produced, complete project products using existing procedures, complete projects on time, product results are in accordance with established indicators and are able to present project results substantively correctly. Thus, the team based project learning method can act as an alternative learning method in order to support the implementation of the OBE (Outcome based Education) curriculum in physics learning